Leucine, Not Total Protein, Content of a Supplement Is the Primary Determinant of Muscle Protein Anabolic Responses in Healthy Older Women. Issue 7 (13th June 2018) - Devries, Michaela C; McGlory, Chris; Bolster, Douglas R; Kamil, Alison; Rahn, Maike; Harkness, Laura; Baker, Steven K; Phillips, Stuart M
Abstract: Background: Older adults show a blunted muscle protein synthesis (MPS) response to postprandial hyperaminoacidemia relative to younger adults. Evidence suggests that this anabolic resistance can be overcome by consuming greater quantities of leucine. Objective: The purpose of this trial was to determine whether the addition of leucine to a smaller dose (10 g) of milk proteins would, when compared with a larger dose (25 g) of whey protein isolate (WPI), result in similar increases in acute (hourly) and integrated (daily) myofibrillar protein synthesis (myoPS). Methods: Healthy older (mean ± SD age: 69 ± 1 y) women ( n = 11/group) were randomly assigned with the use of a single-blind, parallel-group design to twice-daily consumption of either WPI [25 g WPI (3 g l -leucine)] or leucine (LEU; 10 g milk protein with 3 g total l -leucine) for 6 d. Participants performed unilateral resistance exercise to allow assessment of the impact of the supplement alone and with resistance exercise. We determined acute ( 13 C6 -phenylanine) and integrated [using deuterated water (D2 O)] rates of myoPS in the fasting (acute), basal (integrated), nonexercised, and exercised states. Results: Acute myoPS increased in both legs in response to LEU (fed: 45%; fed+exercise: 71%; P < 0.001) and WPI (fed: 29%; fed+exercise: 47%; P < 0.001) compared with fasting; the increase was greater with LEU than with WPI in the exercised leg (46%; P = 0.04) but not in the rested leg ( P = 0.07). The acute myoPS response was greater in the exercised leg than in the rested leg for both WPI (63%) and LEU (58%) ( P < 0.001). Integrated myoPS increased with WPI and LEU in the exercised leg (both 9%; P < 0.001) during supplementation, and with WPI (3%; P = 0.02) but not LEU (2%, P = 0.1) in the rested leg compared with the basal state. Conclusions: A lower-protein (10 compared with 25 g/dose), leucine-matched beverage induced similar increases in acute and integrated myoPS in healthy older women. Lower-protein supplements with added leucine may represent an advantageous approach in older adults to maintain skeletal muscle anabolic sensitivity and attenuate muscle loss; however, further work is needed using longer-term interventions to substantiate these findings. This trial was registered at www.clinicaltrials.gov as NCT02282566.